2019 American College of Rheumatology/Arthritis Foundation Guideline for the Treatment of Juvenile Idiopathic Arthritis: Therapeutic Approaches for Non-Systemic Polyarthritis, Sacroiliitis, and Enthesitis - Ringold, Sarah (Arthritis Rheumatol, 2019)
OBJECTIVE: To develop treatment recommendations for children with juvenile idiopathic arthritis manifesting with non-systemic polyarthritis, sacroiliitis, or enthesitis. METHODS: PICO (population/intervention/comparator/outcome) questions were developed and refined by members of the guideline development teams. A systematic review was conducted to compile evidence for the benefits and harms associated with treatments for these conditions. Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology was used to rate the quality of evidence. A group consensus process was conducted among the Voting Panel to generate the final recommendations and grade their strength. A Parent and Patient Panel used a similar consensus approach to provide patient/caregiver preferences for key questions. RESULTS: 39 recommendations were developed (8 strong and 31 conditional). The quality of supporting evidence was “very low” or “low” for 90% of recommendations. Recommendations are provided for the use of nonsteroidal anti-inflammatory drugs (NSAIDs), disease modifying anti-rheumatic drugs (DMARDs), biologics, and intraarticular and oral glucocorticoids. Recommendations for the use of physical and occupational therapy are also provided. Specific recommendations for polyarthritis address general medication use, initial and subsequent treatment, and adjunctive therapies. Good disease control, with therapeutic escalation to achieve low disease activity, was recommended. The sacroiliitis and enthesitis recommendations primarily address initial therapy and adjunctive therapies. CONCLUSION: This guideline provides direction for clinicians, caregivers, and patients making treatment decisions. Clinicians, caregivers, and patients should use a shared decision-making process that accounts for patients’ values, preferences, and comorbidities. These recommendations should not be used to limit or deny access to therapies.